East Asia and Global Imbalances: Saving, Investment, and Financial Development - Ito, Hiro; Chinn, Menzie D. (My University, 2007)
The paper investigates the role of budget balances, financial development and openness in the evolution of global imbalances. The authors examinine the effect of different types and aspects of financial development using a cross-country analysis that encompassinges a sample of 19 industrialized countries and 70 developing countries for 1986 through 2005.